Relevance of Women Reservation in Nepal - Shreshta, Manju (Academic Voices: A Multidisciplinary Journal, 2011)
The major feature of democratic system is the inclusive and equitable representation of every individual from every stratum. True democracy can’t be imagined in absence of equal representation either politically, socially or economically. Female access must be ensured in every mechanism of the state for the justifiable and proportionate participation of women. Their position, as a privilege, must be saved to bring them into the mainstream of the state since they have been suppressed and oppressed from the time immemorial. Women, who hold more than 50% of the total population, must be ensured with their equal representations from local level to central. This paper aims to appraise the situation of women participation in politics and policy making and to highlight the significance of reservation for them. Keywords Women, politics, participation, policy making, reservation DOI: http://dx.doi.org/10.3126/av.v1i0.5308 Academic Voices 2011; 1: 34-38